Nonlinear servo motor simulation and control - Sim, Yeow Hwee. (2011)
Digital Signal Processor over the years gained popularity in the field of high speed control application as they provide a dual-bus architecture to allow simultaneous processing of program instructions and data as well as special hardware multipliers to handle operations rapidly. The use of a high-speed Digital Signal Processors (DSP) is particularly appropriate, facilitating a small sampling period and flexibility for implementation of different control algorithms.